Influence of dietary dried distillers grains and glycerol on bacon quality - Goehring, Brandon Lee (Kansas State University, 2010)
The objectives of this study were to determine the impact of 0 and 20% dried distillers grains with soluble (DDGS) and increasing levels of glycerol (0, 2.5 and 5%) in grow-finishing rations on bacon quality and to determine the relationship between belly firmness and slicing yield for commercially produced bacon. A total of 84 barrows (PIC, initially 31.03 kg) were fed corn-soybean meal-based diets organized in a 2 x 3 factorial with primary effects of DDGS (0 or 20%) and glycerol (0, 2.5, or 5%) as fed. Belly length was measured from flank end to blade end. Belly thickness was measured at eight locations evenly spaced around the perimeter of the belly. Belly firmness was measured by centering bellies perpendicularly (skin side up and skin side down) over a stainless steel smokestick and measuring the flex between the edges on the ventral and dorsal edges of the belly. Bellies were injected at 12% of the skinned belly weight resulting in a final concentration of 1.74% salt, 0.5% sugar, 0.3% sodium phosphate, 120 ppm sodium nitrite, and 500 ppm sodium erythorbate in the bellies. Bellies were cooked to an internal temperature of 53oC, chilled, pressed and sliced for evaluation. Belly slice yield was calculated by determining the yield of #1 type bacon slices. Proximate analysis and fatty acid analysis were evaluated by taking every 10th bacon slice beginning from the caudal end to make a composite sample for each belly. Iodine value was calculated using the resulting fatty acid content results. Twenty bacon slices were removed from the belly one-third the length of the belly from the cranial end for sensory analysis and cooking yields. Sensory characteristics were evaluated on an 8-point scale for brittleness, bacon flavor intensity, saltiness and off-flavor. There were no significant DDGS x glycerol interactions on any parameters measured (P > 0.08). Inclusion of 20% DDGS in pig diets decreased belly firmness (P < 0.04) as measured by the belly flop fat side down method. Twenty percent DDGS decreased the percentage of myristic acid, palmitic acid, palmitoleic acid, stearic acid, oleic acid, vaccenic acid, total saturated fatty acids, and total monounsaturated fatty acids (P < 0.01). In contrast, 20% DDGS increased the percentage of linoleic acid, α-linolenic acid, eicosadienoic acid, total polyunsaturated fatty acids and decreased unsaturated: saturated fatty acid ratios, polyunsaturated: saturated fatty acid ratios, and iodine values (P < 0.01). Statistical correlation analysis of belly processing characteristics showed that by increasing belly weight there will be an increase in smokehouse yields (R = 0.81), increasing smokehouse yields will increase slice yield (R = 0.71), increasing belly thickness results in firmer bellies (R = 0.94) and increasing belly firmness will increase slice yields (R = 0.60). Fatty acid content did not correlate with any belly processing characteristic (R < 0.50). Iodine values were highly correlated with Total MUFA (R = 0.83) Total PUFA (R = 0.79), Total TFA (R = 0.75), and UFA: SFA ratio, and PUFA: SFA ratios (R = 0.83). The inclusion of 0, 2.5 and 5% glycerol in swine diets did not affect any measured parameters in this study. In conclusion, feeding DDGS at a level of 20% decreased belly firmness and changed the fatty acid profile; however, it did not affect belly processing or sensory characteristics. Glycerol fed at 2.5 or 5.0% did not affect belly quality, fatty acid profile, or sensory characteristics of bacon.
Keywords: Bacon; Belly quality; Dried distillers grains; Glycerol; Pork; Agriculture, Food Science and Technology (0359)